2013
DOI: 10.1007/s10865-013-9530-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a self-management intervention for weight control in overweight and obese adults: a randomized controlled trial

Abstract: Brief self-management interventions to engender successful weight maintenance are seldom tested in obese and overweight populations without diabetes. To test the efficacy of the intervention, aimed at improving proactive coping, in obese and overweight adults at risk for diabetes. Participants (N = 255) were randomly assigned to two experimental groups (N = 185) and a control group (N = 70). Experimental groups received the same intervention in week 1-8 (initial phase) and booster sessions with different conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Second, the duration of the intervention (3 months) may have been of insufficient duration to achieve adequate and prolonged weight loss among the present study population. Also the inclusion of the booster sessions had no added value, which is consistent with previous studies [ 44 , 45 ]. It can also be suggested that the current intervention is more suitable for weight gain prevention.…”
Section: Discussionsupporting
confidence: 91%
“…Second, the duration of the intervention (3 months) may have been of insufficient duration to achieve adequate and prolonged weight loss among the present study population. Also the inclusion of the booster sessions had no added value, which is consistent with previous studies [ 44 , 45 ]. It can also be suggested that the current intervention is more suitable for weight gain prevention.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the high participant burden from comprehensive diary keeping or daily website logs, as well as a lack of personal control evident in intensive trials limits acceptability. This is demonstrated by poor attendance [ 31 ], failure to complete homework assignments, and low message uptake with attrition rates up to 50% at 12 mo [ 32 ]. In contrast, we demonstrated weight gain prevention is feasible, highly acceptable to participants, and can be achieved with low participant burden [ 16 ] and good retention at around 79%.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with irritable bowel syndrome (IBS) or overweight and obesity, managing these conditions and achieving desired health outcomes relies upon everyday lifestyle choices and monitoring to identify individual symptom triggers or weight loss barriers. Self-management programs and lifestyle counseling are clinically effective in these two populations [25,61], and both of these approaches encourage self-tracking. However, limited time and resources inhibit providers in clinical practice from fully engaging with and reviewing data collected by patients.…”
mentioning
confidence: 99%
“…Patients typically work with a multidisciplinary team of providers -including primary care physicians, gastroenterologists, dietitians, psychologists and/or psychiatrists -to identify and manage the causes and symptoms. Behavioral interventions and self-management are integral to effective treatment [25,61], so patients may be asked to record food intake, exercise, stress, abdominal pain, heart rate, and sleep patterns, among other indicators. Prior work has examined self-tracking tools in various domains [e.g., myFitnessPal, 58; SleepCycle, 30], but their use in patient-provider collaboration is not well understood.…”
mentioning
confidence: 99%